Prophylaxis of Wound Infections-antibiotics in Renal Donation (POWAR): A UK Multicentre Double Blind Placebo Controlled Randomised Trial. Issue 1 (July 2020) - Ahmed, Zubir; Uwechue, Raphael; Chandak, Pankaj; van Dellen, David; Barwell, Jamie; Heap, Sarah; Szabo, Laszlo; Hemsley, Carolyn; Olsburgh, Jonathon; Kessaris, Nicos; Mamode, Nizam
Abstract : Background: Postoperative infection after hand-assisted laparoscopic donor nephrectomy (HALDN) confers significant morbidity to a healthy patient group. Current UK guidelines cite a lack of evidence for routine antibiotic prophylaxis. This trial assessed if a single preoperative antibiotic dose could reduce post HALDN infections. Methods: Eligible donors were randomly and blindly allocated to preoperative single-dose intravenous co-amoxiclav or saline. The primary composite endpoint was clinical evidence of any postoperative infection at 30 days, including surgical site infection (SSI), urinary tract infection (UTI), and lower respiratory tract infection (LRTI). Findings: In all, 293 participants underwent HALDN (148 antibiotic arm and 145 placebo arm). Among them, 99% (291/293) completed follow-up. The total infection rate was 40.7% (59/145) in the placebo group and 23% (34 of 148) in the antibiotic group ( P = 0.001). Superficial SSIs were 20.7% (30/145 patients) in the placebo group versus 10.1% (15/148 patients) in the antibiotic group ( P = 0.012). LRTIs were 9% (13/145) in the placebo group and 3.4% (5/148) in the antibiotic group ( P = 0.046). UTIs were 4.1% (6/145) in the placebo group and 3.4% (5/148) in the antibiotic group ( P = 0.72). Antibiotic prophylaxis conferred a 17.7% (95% confidence interval 7.2%–28.1%), absolute risk reduction in developing postoperative infection, with 6 donors requiring treatment to prevent 1 infection. Interpretation: Single-dose preoperative antibiotic prophylaxis dramatically reduces post-HALDN infection rates, mainly impacting SSIs and LRTIs. Abstract : Supplemental Digital Content is available in the text